Process optimisation, biocompatibility and anti-cancer efficacy of curcumin loaded gelatine microparticles cross-linked with dialdeyhde carboxymethyl cellulose - Kocer, Zeynep; Aru, Basak; Sezer, Umran Aydemir; Demirel, Gulderen Yanikkaya; Beker, Ulker; Sezer, Serdar (TAYLOR & FRANCIS LTD, 2019)
In this study, we produced curcumin loaded gelatine microparticles, through spray-drying method, with dialdehyde carboxymethyl cellulose (DCMC) which is introduced as a new cross-linking agent for drug delivery systems and examined toxicities by comparison of traditional cross-linking agents. We employed various parameters in the production and tried to develop the most efficient drug delivery system through Taguchi method by examining efficiencies on gastric cancer under in vitro conditions. The results indicated gelatine microparticles cross-linked with DCMC offers more biocompatible drug delivery systems. The particle size of the microparticles produced via different parameters varies from 1.926 to 3.357 mu m. Curcumin was substantially remained stable after 6 months. This study indicates potential use of DCMC cross-linked gelatine microparticles as drug delivery vehicle.
Keywords: Gelatine; carboxymethyl cellulose dialdehyde; spray-dry; drug delivery; DELIVERY-SYSTEMS; TURMERIC OLEORESIN; SPRAY; DRUG; CANCER; DIALDEHYDE; LINKING; NANOPARTICLES; STABILITY; RELEASE; Chemistry; Engineering; Pharmacology & Pharmacy